PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA KELAS VIII SMPN 5 PELEPAT - viyona Sari Apriliana; Sugeng Riyadi; Awatif (Matedukasia, 2023)
This study aims to find out and describe students' mathematical critical thinking skills taught using the Problem Based Learning learning model better than those taught by conventional learning in class VIII students of State Junior High School 5 Pelepat Academic Year 2022/2023. This study used experimental methods. Posttest Only Control Group Design research design. The population used in this study was the entire class VIII with a total of 63 students. How to take a sample using Sample Random Sampling. The data were collected using test techniques in the form of descriptions totaling 3 questions. The data analysis in hypothesis testing using Independent Sample t-test. The final test result averaged 60.48 and in the control class was 49.69. Obtained thitung=3.351 and ttabel=1.670 so that the thitung > ttabel thus H1 is accepted. So it can be concluded that the mathematical critical thinking ability taught with the Problem Based Learning learning model is better than that taught by conventional learning of class VIII students of State Junior High School 5 Pelepat.